2018
DOI: 10.1111/jeu.12637
|View full text |Cite|
|
Sign up to set email alerts
|

Dactylomonas gen. nov., a Novel Lineage of Heterolobosean Flagellates with Unique Ultrastructure, Closely Related to the Amoeba Selenaion koniopes Park, De Jonckheere & Simpson, 2012

Abstract: We report the discovery of a new genus of heterolobosean flagellates, Dactylomonas gen. nov., with two species, D. venusta sp. nov. and D. crassa sp. nov. Phylogenetic analysis of the SSU rRNA gene showed that Dactylomonas is closely related to the amoeba Selenaion, the deepest-branching lineage of Tetramitia. Dactylomonads possess two flagella, and ultrastructural studies revealed an unexpected organization of the flagellar apparatus, which resembled Pharyngomonada (the second lineage of Heterolobosea) instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The 18S rRNA gene sequences from the seven unstudied Percolomonas strains were closest by BLASTN search to Percolomonas cosmopolitus strain WS (AF 519443), but with a low identity of 74% to 83%. As in previous studies [1416, 19, 31, 32], Heterolobosea formed a strong monophyletic group in phylogenetic trees of 18S rRNA gene sequences (Fig 3). The seven new Percolomonas strains and two previously identified sequences branched with the pseudociliate taxon Stephanopogonidae with strong support (100% ML; PP 1; Fig 3) forming the clade Percolatea.…”
Section: Resultssupporting
confidence: 81%
“…The 18S rRNA gene sequences from the seven unstudied Percolomonas strains were closest by BLASTN search to Percolomonas cosmopolitus strain WS (AF 519443), but with a low identity of 74% to 83%. As in previous studies [1416, 19, 31, 32], Heterolobosea formed a strong monophyletic group in phylogenetic trees of 18S rRNA gene sequences (Fig 3). The seven new Percolomonas strains and two previously identified sequences branched with the pseudociliate taxon Stephanopogonidae with strong support (100% ML; PP 1; Fig 3) forming the clade Percolatea.…”
Section: Resultssupporting
confidence: 81%
“…The latter group is ecologically and morphologically extremely diverse and contains the vast majority of described species; however, its internal phylogeny is still almost exclusively based on SSU rRNA data. Because the traditional classification of Heterolobosea does not correspond with its internal phylogeny as it is currently understood, our database adopted provisional terminology as presented by Pánek et al ( 36 ) and Hanousková et al ( 37 ). In short, we recognize eight main clades of Tetramitia: Selenaionida (syn.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Heterolobosea was revealed to be the second most abundant group www.nature.com/scientificreports www.nature.com/scientificreports/ (38.6% of total read counts) in the supergroup 'Excavata' using the V9 region, but this group was not detected using the V4 region. Heterolobosea, including amoeba, amoeboflagellate, and flagellate forms, represents one of rare taxa in environmental surveys 17,30,35 , but were commonly isolated from freshwater, marine, soil, and extreme environments [36][37][38][39][40][41][42][43][44][45][46] . Pawlowski et al 17 reported that Heterolobosea comprises <1% of total reads using NGS technology with only the V9 region.…”
Section: Scientific Reports |mentioning
confidence: 99%